Square Root of iDate: 12/06/2001 at 20:38:22 From: Morgan McBee Subject: Square root of i What is the square root of i (square root of the square root of negative one)? On my calculator, I get square root of two divided plus i times the square root of two divided by two, but I do not understand why. Date: 12/06/2001 at 21:04:45 From: Doctor Tom Subject: Re: Square root of i Hi Morgan, You can test that your calculator is right: simply multiply that number by itself and you'll get i. The reason is not obvious. See Imaginary Exponents and Euler's Equation from the Dr. Math FAQ: http://mathforum.org/dr.math/faq/faq.euler.equation.html - Doctor Tom, The Math Forum http://mathforum.org/dr.math/ Date: 12/06/2001 at 22:09:49 From: Doctor Pete Subject: Re: Square root of i Hi, To try to answer your question in a satisfying way, I'll introduce a definition for the imaginary unit i that does not involve square roots of negative numbers. We set up a system of addition and multiplication of ordered pairs (a,b), where a and b are real numbers, in the following manner: For any two pairs (a,b) and (c,d), we have (a,b) + (c,d) = (a+c, b+d), (a,b) * (c,d) = (ac-bd, ad+bc). Then we see that numbers of the form (a,0) correspond to real numbers, since (a,0) + (c,0) = (a+c, 0) and (a,0) * (c,0) = (ac - 0, 0) = (ac, 0). That is, there is a one-to-one correspondence between the ordered pair (a,0) and the real number a. So we might as well say (a,0) = a. Furthermore, we note that (0,1) * (0,1) = (0 - 1, 0 + 0) = (-1, 0) = -1. So the ordered pair (0,1) has the property that its square is -1. Therefore, we define i = (0,1), and we can say for all real numbers a, b, that a + bi = (a,b), since a + bi = (a,0) + (b,0)*(0,1) = (a,0) + (b*0 - 0*1, b*1 + 0*0) = (a,0) + (0,b) = (a,b). So instead of thinking of complex numbers as things like 3 + 4i, we can think of them as ordered pairs like (3,4), which follow the rules of addition and multiplication that we specified earlier. Now, the "square root of i" under this new definition is an ordered pair (x,y), with x, y real numbers, such that (x,y)^2 = (x,y)*(x,y) = (0,1). But we use the definition of multiplication to find (x,y)^2 = (x^2 - y^2, 2xy) = (0,1). If we match up the corresponding parts of the ordered pairs, we get the system of equations x^2 - y^2 = 0, 2xy = 1. If we consider the first equation, we have x^2 - y^2 = (x+y)(x-y) = 0, which means x+y = 0, or x-y = 0. In the first case, x = -y, and substituting this into the second equation gives 2(-y)y = 1, which has no real solution for y. In the second case, x = y, and substituting into the second equation then gives 2y^2 = 1, or y = {1/Sqrt[2], -1/Sqrt[2]}. Hence, we have found two solutions, namely (x,y) = {(1/Sqrt[2], 1/Sqrt[2]), (-1/Sqrt[2],-1/Sqrt[2])}, and if we want to write this in the more conventional x + yi notation, x + yi = {(1+i)/Sqrt[2], (-1-i)/Sqrt[2]}. I hope you don't think my explanation was too complicated. It is a little unconventional, because most people would explain it by talking about the polar form of complex numbers, and De Moivre's Theorem. - Doctor Pete, The Math Forum http://mathforum.org/dr.math/ |
Search the Dr. Math Library: |
[Privacy Policy] [Terms of Use]
Ask Dr. Math^{TM}
© 1994-2013 The Math Forum
http://mathforum.org/dr.math/